Investigating the reasons for failures and delays in R&D projects with the project management approach - Saeed Ghorbani; Shayan Naghdi Khanachah (goodwood publishing, 2020)
Purpose: This study aimed to identify and investigate the reasons for failures and delays in R&D projects with an organizational productivity approach. Research methodology: In order to identify the most influential factors in the research area, a questionnaire with a Likert spectrum of five options was designed and distributed among the stakeholders of research projects. The questionnaire results were analyzed and 10 more effective factors were identified and solutions were used to improve the situation. Result: In the present study, after reviewing the background of the subject and reviewing previous studies, 149 factors affecting the failure and delay of projects were identified and after aggregating and summarizing the factors, a model was designed to classify the causes of delay in which 55 effective factors in two general categories. Intra-organizational and extra-organizational factors were examined. Limitations: This research only described Research-oriented organizations. Contribution: According to the analysis results regarding the more effective causes, problems and challenges related to each of the factors were studied and to reduce the impact of existing factors, various solutions and suggestions in the field of research variables using Expert opinion was provided.